DART-bid (Dose-differentiated accelerated radiation therapy, 1.8 Gy twice daily)–a novel approach for non-resected NSCLC: final results of a prospective study, correlating radiation dose to tumor volume - Wurstbauer, Karl (BioMed Central, 2013)
BACKGROUND: Sequential chemo-radiotherapies with intensive radiation components deliver promising results in non-resected non-small cell lung cancer (NSCLC). In general, radiation doses are determined by dose constraints for normal tissues, not by features relevant for tumor control. DART-bid targets directly the doses required for tumor control, correlating doses to tumor volume in a differentiated mode. MATERIALS/METHODS: Radiation doses to primary tumors were aligned along increasing tumor size within 4 groups (<2.5 cm/2.5–4.5 cm/4.5–6.0 cm/>6.0 cm; mean number of three perpendicular diameters). ICRU-doses of 73.8 Gy/79.2 Gy/84.6 Gy/90.0 Gy, respectively, were applied. Macroscopically involved nodes were treated with a median dose of 59.4 Gy, nodal sites about 6 cm cranial to involved nodes electively with 45 Gy. Fractional doses were 1.8 Gy twice daily (bid). 2 cycles chemotherapy were given before radiotherapy. Between 2004 and 2009, 160 not selected patients with 164 histologically/cytologically proven NSCLC were enrolled; Stage I: 38 patients; II: 6 pts.; IIIA: 69 pts.; IIIB: 47 pts. Weight loss >5%/3 months: 38 patients (24%). Primary endpoints are local and regional tumor control rates at 2 years (as >90% of locoregional failures occur within 2 years). Secondary endpoints are survival and toxicity. With a minimum follow-up time of 2 years for patients alive, the final results are presented. RESULTS: 32 local and 10 regional recurrences occurred. The local and regional tumor control rates at 2 years are 77% and 93%, respectively. The median overall survival (OS) time is 28.0 months, the 2- and 5-year OS rates are 57% and 19%, respectively. For stage III patients, median OS amounts to 24.3 months, 2- /5-year OS rates to 51% and 18%, respectively. 2 treatment-related deaths (progressive pulmonary fibrosis) occurred in patients with pre-existing pulmonary fibrosis. Further acute and late toxicity was mild. CONCLUSIONS: This novel approach yields a high level of locoregional tumor control and survival times. In general it is well tolerated. In all outcome parameters it seems to compare favourably with simultaneous chemo-radiotherapies, at present considered ‘state of the art’; and is additionally amenable for an unselected patient population.